SPUNTI DI RIFLESSIONE SUL CURRICOLO VERTICALE DI EDUCAZIONE LINGUISTICA (ItalianoLinguadue, 2025)
Some remarks about the vertical curriculum of language education                 Starting from the identification of the linguistic skills and from the metalinguistic capacity as basic dimensions of a language education project, the setting criteria of a vertical curriculum are the thematic thread that runs through the issues discussed in the article: what is meant by continuity and gradualness in the grammatical syllabus and in the receptive and productive linguistic skills development; how to create opportunities for intersections and functional reciprocity among these language education dimensions that moreover include characteristic features of the communication coenveyed by the digital technologies with their peculiar textual genres. There are other underlying questions: on the one hand the initial teachers education system, the rooting of educational linguistics and methodological awareness in their professional competence, on the other the obstacles of certain rigid stereotypes of educational communication